MODELLING THE SORPTION OF ZN AND NI ON CA-MONTMORILLONITE - COULOMBIC EFFECTS ON THE ADSORPTION OF TRACE CATIONS ON CLAYS - Bradbury M.H.; Baeyens B. (My University, 1999)
In some previous work titration and Ni/Zn sorption edge/isotherm measurements carried out under a wide variety of experimental conditions on purified Na-montmorillonite were modelled in terms of cation exchange and surface complexation mass action equations. A major objective of the experimental/modelling programme is to understand and predict sorption in commercial bentonite systems. Since montmorillonite is the dominant clay mineral in bentonite and is often present in a mixed Na/Ca form, a natural extension to the previous investigations was to study Ni/Zn sorption on a conditioned Ca-montmorillonite. An important open question was whether the same basic parameters such as site types, site capacities, and acidity constants could be used for both materials and to see to what extent the Ni and Zn surface complexation constants were influenced by the form of the montmorillonite. Sorption edges for Ni and Zn at different Ca(NO3)2 background electrolyte concentrations, together with sorption isotherms measured over a range of pH values, are presented and modelled using the MINSORB code. The parameters characterising the sorption of Ni and Zn on Na- and Ca-montmorillonite systems are compared. Finally, examples are given that illustrate how the modelling can provide insight into the sorption processes.